Fair Resource Allocation Algorithm for OFDMA System with Imperfect CSI - Yaohui Wu; Youming Li; Liping Jin; Pengfei Shao (Dianxin kexue)
Existing resource allocation algorithms can't balance system capacity and fairness well when the channel state information is imperfect. In order to solve this problem, a fair resource allocation algorithm was proposed to maximize the system ergodic capacity, while the fairness could be adjusted flexibly by introducing the fairness relaxation factor. In order to reduce the complexity in the use of dual optimization method for solving the lagrange operator process, an iteration searching method in the same layer was proposed to replace the traditional multi-layer iteration searching method. Simulation results show that the proposed algorithm can effectively maximize the system ergodic capacity and guarantee the fairness, while the computational complexity was reduced significantly.